Perbandingan Konstruktivis dan Parennialis dalam Menjelaskan Pengalaman Mistik: Constructivist and Parennialis in Explaining Mystical Experiences - Ilham Maulana (UIN Sunan Kalijaga Yogyakarta, 2022)
In the discourse of philosophy of mysticism, there are at least two opposing views in explaining the expression of mystical experience, namely constructivist and perennialist. The constructivist views that mystical expression is closely related to the mystical tradition that originates so that the symbols used cannot be separated from tradition. This relates to the cognitive qualities possessed by mystics which shape the reality they find. Meanwhile, the perennialist argues that mystical expressions can be separated from tradition, so mystics often use symbols that are universal and cross-tradition. Discovered reality transcends cognitive influence. This article will analyse the comparison of the two views. The method used in this research is comparative analysis to find a middle ground that the two views are possible to juxtapose. I found a meeting point between the two views is the issue of ineffability or the unspeakable nature which is one of the characteristics of mystical experience. This problem shows that the relationship between experience and understanding in the case of spiritual experience is so complex. There are facts that are experienced but cannot be expressed so that mystics choose to remain silent or make paradoxical expressions. Therefore, the solution given is the ineffability character of mystical experience which cannot be ignored by constructivists and at the same time does not show that mystical experience is a pure experience as perennialist claim. Keywords : Constructivist, ineffability, mystical experience, mystical expression, parennialist